Analisis Efisiensi Produksi, Risiko Kecelakaan Kendaraan, dan Dinamika Pasar Kendaraan Listrik: Studi Data Industri Otomotif Global 1980–2023 - Hildan Wijianto; Maulana Hafizh Fadly; Yusup Septiana; Zurnan Alfian; Sopyan Apandi (Jurnal Teknik Informatika dan Teknologi Informasi, 2025)
This study aims to examine the dynamics of the automotive industry in terms of production efficiency, driving safety, and the market shift towards electric vehicles. The data used include North American automotive production efficiency (1998), the risk of fatalities due to accidents in various countries (1980–1982), and the sales trend of Tesla vs BYD electric vehicles (2021–2023). The analysis methods include descriptive statistics, WPV/HPV comparisons between manufacturers, and market trend analysis. The results show that factory efficiency plays an important role in price stability, countries with good transportation infrastructure have a low risk of accidents, and BYD shows more aggressive market growth than Tesla. This study provides insights for the industry and policymakers regarding the challenges of efficiency, safety, and the transition to electric vehicles.